War and the Engineers : The Primacy of Politics over Technology - Lieber, Keir A. (Book collections on Project MUSE., 2018)
Do some technologies provoke war? Do others promote peace? Offense-defense theory contends that technological change is an important cause of conflict: leaders will be tempted to launch wars when they believe innovation favors attackers over defenders. Offense-defense theory is perhaps best known from the passionate and intricate debates about first-strike capability and deterrence stability during the cold war, but it has deeper historical roots, remains a staple in international relations theorizing, and drives modern arms control policymaking.In War and the Engineers, the first book systematically to test the logical and empirical validity of offense-defense theory, Keir A. Lieber examines the relationships among politics, technology, and the causes of war. Lieber's cases explore the military and political implications of the spread of railroads, the emergence of rifled small arms and artillery, the introduction of battle tanks, and the nuclear revolution. Lieber incorporates the new historiography of World War I, which draws on archival materials that only recently became available, to challenge many common beliefs about the conflict. The author's central conclusion is that technology is neither a cause of international conflict nor a panacea; instead, power politics remains paramount.